A boundary value problem of a semilinear second order ODE - Amster, Pablo Gustavo (2000)
We solve by topological methods a Dirichlet problem for the genera.l scmilinear second order ODE. We also prove the uniqueness of the solutions. Moreover, we develop an iterative method in order to find a solution in certain cases, for which the usual Picard iteration is riot appliable.